17 Delivery of betulinic acid lipid nanoparticles assembled by a microfluidic device. (19th December 2016) - Huang, Xueqin; Zhao, Xi; Wang, Liang; Zhao, Mingzhi; Xie, Peng; Yang, Dongsheng
Abstract : Background: Microfluidics chip-based approaches (MF) can achieve unique transport properties through laminar flows and vastly increased surface-to-volume ratios, which have been extensively utilized to prepare smaller and homogeneous lipid nanoparticles (LNPs). LNPs have shown potential to carry highly insoluble medicines, especially betulinic acid (BA) which has significant antitumour activity but is difficult to administer for cancer therapy due to its poor water solubility. In this study, we investigated the parameters involved in the continuous production of LNPs encapsulating BA (BA-LNPs) by MF, and the possibility of improving antitumour efficacy and reducing toxicities was described. Methods: Briefly, a three-inlet MF system was developed and used to produce the LNPs. EggPC, cholesterol and BA (45:37:18% molar) were dissolved in ethanol. The lipid solution was then loaded into a 1 mL glass syringe and injected into the centre inlet channel, while phosphate-buffered saline (PBS; pH 6.5) was loaded into two 5 mL glass syringes and introduced into the two side inlet channels to establish hydrodynamic focusing. To investigate the physicochemical and biological properties of fabricated liposome at different shear forces, the total flow rate (TFR) is varied from 0.3 to 0.8 mL/min. Results: The TFR has a very small effect on particle size distribution, but an increase in TFR causes a progressive decrease in liposome size. The percentage of encapsulating efficiency (EE) was 77–92% and there were no significant changes when BA-LNPs were stored at 4° C. The inhibitory rate of BA-LNPs was significantly higher compared to free BA in vitro. Immunohistochemical analysis showed many damaged tumor cells after BA-LNPs were injected for 15 days. The survival of mice treated with BA-LNPs was apparently prolonged compared to mice treated with free BA. Conclusions: This result indicates that much stronger antitumour effects were induced by BA-LNP administration, which is most likely due to the relatively small particle sizes produced by MF and which are suitable for intracellular transportation.